Association of Cytokine Gene Polymorphisms in Patients with Tuberculosis and Their Household Contacts. (March 2014) - Sivangala, R.; Ponnana, M.; Thada, S.; Joshi, L.; Ansari, S.; Hussain, H.; Valluri, V.; Gaddam, S.
Abstract Cytokine gene polymorphisms are known to be associated with functional differences in cytokine regulation and may affect host susceptibility to tuberculosis (TB). Contacts are important group in developing tuberculosis infection and are 10–60 times more likely to develop TB than general population. The present study was carried out in patients with TB (N = 176), their household contacts (HHC; N = 155) from Free Chest TB Clinic PPM DOTS (1TU) covering 500, 000 population at Mahavir Hospital and Research Centre, Hyderabad, and healthy controls (HC; N = 170) also included. The association of single‐nucleotide polymorphisms (SNPs) in the promoter region of TNF‐α (−308G/A), IL‐2 (−330T/G), IL‐4 (−589C/T) and in exon region of TGF‐β1 (+869T/C) genes was assessed by ARMS & PCR‐RFLP using specific primers in the above‐mentioned subjects. The differences in allelic or genotypic frequencies of TNF‐α (−308G/A) between patients, their HHC and HC were not statistically significant (P > 0.05). IL‐2 (−330T/G) TG genotype was significantly different between patients, HHC compared to HC (P < 0.002, OR‐1.997, 95%CI‐1.260‐3.168, P < 0.03, OR‐1.602, 955CI‐1.003‐2.561).IL‐4 (−589C/T) CC genotype was significantly different between patients and HC (P < 0.03, OR‐1.791, 95%CI‐1.009‐3.189) as well as between HHC and HC at P < 0.0001, OR‐2.56, 95%CI‐1.448‐4.545. In addition, the TGF‐β 1 (+869T/C) TC genotype was significantly associated with susceptibility to tuberculosis in patients when compared against HC(P < 0.0001, OR‐3.416, 95%CI‐2.063‐5.670) and HHC (P < 0.0001, OR‐2.357, 95%CI‐1.439‐3.868), respectively.MDR analysis indicated that TT genotype of TGF‐β1 with TT and CT genotypes of IL‐4 showed high risk with GA, TT genotypes of TNF‐α, IL‐2, respectively. Our results suggest that IL‐2 (‐330T/G), IL‐4 (‐589 C/T) and TGF‐β1 (+869T/C) gene polymorphisms may be associated with TB susceptibility.